The Role of Prosecutors in the Implementation of Judges' Decisions on Corruption Crimes (Case Study at the Ende District Attorney's Office) - Partimi, Yuli; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
Abstract. The role of prosecutors is very important in the implementation of criminal decisions for corruption crimes, considering that prosecutors are responsible for ensuring that court decisions can be implemented effectively in order to uphold justice and restore public confidence in the legal system. This study aims to determine and analyze the role of prosecutors in the implementation of judges' decisions on corruption crimes at the Ende District Attorney's Office along with the obstacles faced and their solutions. This study uses a sociological juridical approach method, the research specification is descriptive analytical. The data used are primary data and secondary data while the data collection method is carried out through field studies and literature studies. The data analysis method is qualitative. The theories used are the theory of law enforcement and the theory of how the law works. Based on the research results it can be concluded that he role of prosecutors in implementing judges' decisions on corruption crimes at the Ende District Attorney's Office has been carried out with their authority as stipulated in the law. The obstacles in implementing judges' decisions on corruption crimes at the Ende District Attorney's Office are the lack of functional prosecutors, difficulties in asset tracing, and the failure to implement replacement money decisions. Therefore, the solution is to add prosecutors for special crimes, conduct asset tracing from the investigation stage until before the implementation of the criminal sentence or imprisonment is completed, and take a preventive approach to the convict's family.